A reference section through fast-spread lower oceanic crust, Wadi Gideah, Samail Ophiolite (Sultanate of Oman): Petrographic Data Table and Mineral analyses performed by EPMA - Koepke, Jürgen; Garbe-Schönberg, Dieter; Müller, Tim; Mock, Dominik; Müller, Samuel; Nasir, Sobhi (PANGAEA, 2021)
In the absence of a complete profile through fast-spreading modern oceanic crust, we established a reference profile through the paleo crust of the Samail Ophiolite (Sultanate of Oman), which is regarded as the best analogue for fast-spreading oceanic crust on land. To establish a coherent data set, we sampled hard rocks in the Wadi Gideah in the Wadi-Tayin massif from the mantle section up to the sheeted dikes. This paper reports our studies of the lower crust, a 5 km thick pile of gabbros, focusing on petrographic features and on the results of mineral analyses. We collected petrographical data from thins sections of the samples by optical microscope and performed also EPMA analyses (Electron Probe Microanalysis) of the mineral phases of the rocks. The samples have been collected during field campaigns from 2010 to 2015, and the data have been collected in a period from 2013 to 2021.
Keywords: Electronprobe Microanalysis; Fast-spreading oceanic crust; gabbro; Mineral Analyses; Oman Ophiolite; Petrographic Data; Samail Ophiolite